2004
DOI: 10.1007/s11167-005-0174-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of perfluoroalkanes by high-temperature reaction of graphite with fluorine in a fluidized bed

Abstract: Synthesis of lower perfluoroalkanes (tetrafluoromethane, hexafluoroethane, octafluoropropane, decafluorobutane) by high-temperature reaction of graphite with fluorine in a fluidized bed was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…A similar mechanism was postulated by J. Burdon et al [16,17], for the reaction of ethane with either CoF 3 or KCoF 4 , and by Kornilov et al [18] for the fluorination of ethene on CoF 3 , CeF 4 and MnF 3 at temperatures lower than 450°C. Based on the product distribution, the latter including fluoroalkanes (1,1-difluoroethane and 1,1,2-trifluoroethane, 1,1,1,2-tetrafluorethane), polyfluoroalkanes, and alkenes with more than 4 C atoms, the authors suggested the following reaction pathway: In the reaction of ethylene with CoF 4 , CoF 3 and MnF 3, Kornilov [19] observed a direct correlation between the 1,1,1,2-tetrafluorethane-to-1,1,2,2-tetrafluoroethane ratio and the type of fluorinating metal used.…”
Section: Reaction Mechanismsupporting
confidence: 65%
“…A similar mechanism was postulated by J. Burdon et al [16,17], for the reaction of ethane with either CoF 3 or KCoF 4 , and by Kornilov et al [18] for the fluorination of ethene on CoF 3 , CeF 4 and MnF 3 at temperatures lower than 450°C. Based on the product distribution, the latter including fluoroalkanes (1,1-difluoroethane and 1,1,2-trifluoroethane, 1,1,1,2-tetrafluorethane), polyfluoroalkanes, and alkenes with more than 4 C atoms, the authors suggested the following reaction pathway: In the reaction of ethylene with CoF 4 , CoF 3 and MnF 3, Kornilov [19] observed a direct correlation between the 1,1,1,2-tetrafluorethane-to-1,1,2,2-tetrafluoroethane ratio and the type of fluorinating metal used.…”
Section: Reaction Mechanismsupporting
confidence: 65%
“…Perfluorinated alkanes with a molecular formula C n F 2 n +2 have outstanding properties, very different from those of normal hydrocarbons that make them ideal candidates for a variety of applications ranging from lubricants to artificial blood substitutes. Their chemical structure and the weak intermolecular interactions are mainly responsible for their unique properties …”
Section: Introductionmentioning
confidence: 99%